Synthesis of Polyethylene Glycol-Modified Salicylaldehyde–Chitosan Schiff Base and Its Antibacterial Assay - Umi Shofiyatun Ni’mah; Kamilia Hijriani Zain; Ngadiwiyana Ngadiwiyana; Purbowatiningrum Ria Sarjono; Ismiyarto Ismiyarto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Antibacterial materials are essential for inhibiting the growth of pathogenic microorganisms, and chitosan has received considerable attention due to its intrinsic antibacterial properties, biocompatibility, and biodegradability. However, the limited hydrophilicity and moderate mechanical strength of pristine chitosan restrict its broader application. In this study, chitosan was chemically modified through Schiff base formation with salicylaldehyde, followed by modification with polyethylene glycol (PEG), to enhance its physicochemical properties while maintaining detectable antibacterial performance. The objectives of this research were to synthesize Salicylaldehyde–chitosan Schiff base and PEG-modified Salicylaldehyde–chitosan Schiff base, to characterize their structural and physical properties, and to evaluate their antibacterial performance. The molecular weight of chitosan was determined by viscometry, and the degree of deacetylation was evaluated by Fourier transform infrared (FTIR) spectroscopy. The chitosan used exhibited a molecular weight of 147,926 g/mol and a degree of deacetylation of 67%. Schiff base formation was carried out by refluxing chitosan with salicylaldehyde at 60°C for 3 hours, using various molar ratios. The highest degree of substitution (68.75%) and yield (41.08%) were obtained, with the moderate yield attributed to incomplete conversion and material loss during purification steps. Structural confirmation was achieved through FTIR and UV–Vis spectroscopy by the appearance of characteristic imine (C=N) absorption bands. Subsequent modification with PEG at room temperature for 24 hours yielded 40.49%. The PEG-modified material exhibited significantly enhanced hydrophilicity, as indicated by a swelling ratio of 333.33% and a reduced contact angle of 63.04°. Antibacterial activity evaluated by the disc diffusion method showed inhibition zones of 9 mm against Escherichia coli and 10 mm against Staphylococcus aureus, which are modestly higher than those of the solvent control under the tested conditions. These results suggest that PEG modification improves the hydrophilicity of the chitosan-based Schiff base material while maintaining measurable antibacterial activity, indicating potential for further development in antimicrobial and biomedical materials.